2022
DOI: 10.1002/anie.202205609
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Sustainable Chemistry with Ionic Liquids and Deep Eutectic Solvents: A Fad or the Future?

Abstract: Ionic liquids (ILs) and deep eutectic solvents (DESs) debuted with a promise of a superior sustainability footprint due to their low vapor pressure. However, their toxicity and high cost compromise this footprint, impeding their real-world applications. Fortunately, their property tunability through a rational selection of precursors, including bioderived ones, provides a strategy to ameliorate toxicity, lower cost, and endow new functions. This Review discusses whether ILs and DESs are sustainable solvents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 196 publications
0
47
0
Order By: Relevance
“…[51][52][53] DESs have emerged as a sustainable solvent media for several applications. 54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 99%
“…[51][52][53] DESs have emerged as a sustainable solvent media for several applications. 54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 99%
“…However, even though ILs with their low vapor pressure have been proposed as green solvents, often a dearth of their toxicity and biodegradability assessment is observed [11,12]. These are key elements in the evaluation of the environmental effect of chemicals [13][14][15][16][17]. Ideally, from an environmental point of view, a green solvent should be non-toxic, biodegradable, use bioresources as starting materials and synthesized using effective environmentally friendly synthesis procedures and be recyclable [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…2 ILs can act as the “solvent”, stabiliser, ligand and support for transition metals (complexes and surfaces) as well as bio-, photo- and electro-catalysts, potentially yielding more efficient, green and sustainable processes. 1,3–12 There are dozens of specialised reviews on the use of ILs and derivatives in catalysis reported in the last decade. 13–37 We will concentrate on the possibilities and advantages that ILs and their derivatives may provide for green catalytic reactions as compared to classical molecular organic solvents or water.…”
Section: Introductionmentioning
confidence: 99%